REVERSE BREECH EXTRACTION VS HEAD PUSHING FOR DELIVERY OF DEEPLY IMPACTED FETAL HEAD IN EMERGENCY CAESAREAN SECTION - Tahir, Naila; Shahid, Ghana; Adil, Muhammad; Fatima, Sadia (Journal of Ayub Medical College Abbottabad, 2020)
Background: Obstructed labour is considered a negligible component of maternal mortality in developed countries but it is a major mortality burden in developing countries. This study was done to compare maternal outcome associated with reverse breech extraction and vaginal head pushing method for the deeply impacted foetal head in emergency caesarean section. Methods: It was done at the Department of Obstetrics and Gynaecology Military Hospital, Rawalpindi from May to Nov 2014. A total of 110 patients meeting our inclusion criteria were randomly divided into two groups, i.e., Group A (delivered by reverse breech extraction) and Group B (delivered by hand push method). Patient demographic data and maternal outcomes were compared among both groups. Data was analysed using SPSS-21. Results: Mean age of the patients was 27.51±6.60 and 27.91±6.85 years in Group-A and B respectively with an age range of 15-45 years while the mean gestational age was 39.93±0.87 weeks and 40.05±0.62 weeks in Group A and B respectively. 27 (49.1%) from Group A and 26 (47.3%) from Group B were primigravida. Extension of uterine incision was observed in 5 (9.1%) patients of group-A and 25 (45.5%) patients of group-B. Mean operative duration was 42.47±3.00 min and 51.73±2.14 min in Group A and B respectively. More blood loss was observed in Group-B when compared with Group-A (1542.36±188.27 ml vs 1090.36±130.08 ml). A statistically significant difference was seen in both groups regarding maternal outcomes (p<0.001). Conclusion: Reverse breech extraction for delivery of deeply impacted foetal head during the emergency caesarean section is a safe and quick technique as compared to the push method. Keywords: Reverse breech extraction; vaginal head pushing; Caesarean section; obstructed labour